1989
DOI: 10.1007/bf00003469
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of c-phycocyanin from the cyanobacteriumSpirulina maxima

Abstract: Spirulina biomass was separated into two fractions which may have various uses. A phycocyanin fraction may provide a food colourant and biomarkers, and a protein-rich leftover may be useful as aquaculture feed. Activated charcoal adsorption, ultrafiltration and spray drying were used effectively to produce a high quality colourant grade phycocyanin, while activated charcoal adsorption, ammonium sulphate precipitation, dialysis and chromatography were effective in preparing reagent grade phycocyanin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 11 publications
4
50
0
1
Order By: Relevance
“…Therefore, we tried to extract the PC from wet biomass form with CaCl 2 as a solvent (40 mM, pH 5, 12 h). It was reported that CaCl 2 is better for providing higher content and purity of crude extract compared with KNO 3 , NaNO 3 , NaCl solution and deionized water [11,30]. Through the new two-stage cultivation method, the crude form of PC with high purity of 2.4-2.7 was finally obtained.…”
Section: Purification Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we tried to extract the PC from wet biomass form with CaCl 2 as a solvent (40 mM, pH 5, 12 h). It was reported that CaCl 2 is better for providing higher content and purity of crude extract compared with KNO 3 , NaNO 3 , NaCl solution and deionized water [11,30]. Through the new two-stage cultivation method, the crude form of PC with high purity of 2.4-2.7 was finally obtained.…”
Section: Purification Processmentioning
confidence: 99%
“…At the ratio of 3.9, it is considered a reactive grade, while PC samples producing values above 4.0 are considered to be of analytical grade [9]. Crude extract has generally shown lower purity than food grade; therefore, a large number of purification processes are required to improve the purity, such as aqueous two-phase extraction [10], ammonium sulfate [11], ion-exchange chromatography [12], rivanol [13], or hydrophobic interaction chromatography [14]. However, these successive purification steps account for 50-90 % of the total production costs and are time-consuming processes [9].…”
mentioning
confidence: 99%
“…Several methods have been used for the purification of Cphycocyanin, especially that from Spirulina, such as ammonium sulfate precipitation, membrane processes and different chromatographic methods (Minkova et al 2003;Silveira et al 2007;Chaiklahan et al 2011;Bermejo and Ramos 2012). C-phycocyanin with a purity of 0.7 is considered as food grade, 3.9 as reactive grade and above 3.9 as analytical grade (Herrera et al 1989;Rito-Palomares et al 2001). The purification processes are generally long and complex and time and solvent consuming; efficiency and low toxicity have limited the application of some methods (Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Phycocyanin is a natural blue colorant, has uses as a food colorant for chewing gum, ice sherbets, soft drinks, candies and cosmetics including lipstick and eyeliners. Small quantities are also used as biochemical tracers in immunoassays due to its fluorescent properties (Herrera et al, 1989;Silveira et al, 2007). Furthermore, phycocyanin has been proven to have therapeutic properties including antioxidant, anti-inflammatory and anti-cancer activities (Romay et al, 2003;Eriksen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many methods previously reported have been used to separate and purify phycocyanin from microalgae (Soni et al, 2006;Silveira et al, 2007;Singh et al, 2009). Precipitation with ammonium sulfate and the use of ultrafiltration (UF) can be used to obtain food grade phycocyanin, which has a purity ratio in the range of 0.7-2.0, whereas, gel filtration chromatography and ion-exchange chromatography can achieve analytical grade phycocyanin (Herrera et al, 1989;Rito-Palomares et al, 2001;Moraes and Kalil, 2009). Herrera et al (1989) reported that purification by UF, using a membrane with a molecular weight cut-off (MWCO) at 50 kDa, followed by activated charcoal adsorption and then spray drying, produced a food grade phycocyanin powder with a purity ratio of 0.74.…”
Section: Introductionmentioning
confidence: 99%